1989
DOI: 10.1111/j.1465-7287.1989.tb00574.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Criminal Sanctions in Antitrust Enforcement

Abstract: Recently enacted sentencing guidelines were designed to reduce disparity and to increase the average sanction for white-collar offenders. Whether these outcomes will be achieved, however, depends on how closely judges adhere to the new guidelines. We cannot yet determine how the guidelines will be implemented but can learn much about judicial behavior by studying past sentencing practice. Copyright 1989 Western Economic Association International.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…That wealth transfer came at the expense of growing firms on the threshold of interstate expansion insofar as the Clayton Act threatened to deny them low-cost means (such as holding companies, merger, exclusive dealing and other socalled vertical restraints of trade), of accomplishing that objective. 33 Private interests of yet other origins were revealed by Mark Cohen (1989Cohen ( , 1992 in two studies of the penalties imposed by judges on firms determined to be guilty of criminal Sherman Act offenses. After assembling a dataset consisting of more than 600 indictments handed down from 1955 through 1980, Cohen found that, other things being the same, jail sentences tended to be longer, fines tended to be higher, and nolo contendere pleas were less likely to be accepted over the government's objection when the judge hearing the case perceived an opportunity for promotion to a higher federal court.…”
Section: The Interest-group Theory Of Antitrustmentioning
confidence: 97%
“…That wealth transfer came at the expense of growing firms on the threshold of interstate expansion insofar as the Clayton Act threatened to deny them low-cost means (such as holding companies, merger, exclusive dealing and other socalled vertical restraints of trade), of accomplishing that objective. 33 Private interests of yet other origins were revealed by Mark Cohen (1989Cohen ( , 1992 in two studies of the penalties imposed by judges on firms determined to be guilty of criminal Sherman Act offenses. After assembling a dataset consisting of more than 600 indictments handed down from 1955 through 1980, Cohen found that, other things being the same, jail sentences tended to be longer, fines tended to be higher, and nolo contendere pleas were less likely to be accepted over the government's objection when the judge hearing the case perceived an opportunity for promotion to a higher federal court.…”
Section: The Interest-group Theory Of Antitrustmentioning
confidence: 97%
“…Such goals mean that senior bureaucrats up the FTC's chain of command will conclude that "structural matters and industrywide cases threaten the morale of the staff because they often involve years of tedious investigation before they reach the trial 11 Federal judges, too, have been found to be influenced by parochial motives in deciding antitrust cases. Cohen (1989Cohen ( , 1992 presents evidence that trial judges are more likely to side with the Antitrust Division when more opportunities for promotion to seats on higher courts are open (the recommendations of the Justice Department are decisive in securing nomination to the federal bench). Judges also impose harsher penalties on guilty antitrust defendants when the queues of cases awaiting trial before them are longer, thereby inducing more defendants to settle out of court and lightening their own workloads.…”
Section: Relevance To Antitrust Law Enforcementmentioning
confidence: 99%